Effects of video-based technology to improve performance of a soccer player’s direct free kick - Tan, Mark Mu Zhou (2018)
Many sports are using video replay to improve the skill acquisition of their athlete. However, the differences in video, verbal and self-guided practice methods has yet to be researched in the sport of soccer. The aim of this study is to investigate the differences in these methods to improve a soccer player’s direct free kick. It was hypothesized that there is no significant difference between the three methods for the results between the pre-test and post-test, post-test and retention test. However, there is a significant difference between the pre-test and retention test. Thirty male soccer players (Mean (SD): 23.3 (1.5) years) completed 30 direct free kicks achieving maximum points consisting between zero to five. The mean scores were submitted to a 3(Group: video instruction, verbal instruction, self-guided practice) by 3(Test: pre-test, post-test, retention test) using analysis of variance with a repeated measure at the final factor. The alpha value was set at 0.05. No significant difference was found between the three-group’s mean score difference in pre-test and post-test [F (2,27) = 1.997, p = 0.155], post-test and retention test [F (2,27) = 0.638, p = 0.536]. A significant difference was found in the pre-test and retention test [F (2,27) = 3.488, p = 0.045]. Tukey HSD test indicated the significant difference lies within self-guided method (M= 1.70, SD= 9.83) and video method (M= 15.20, SD= 12.42). These results implied that video method could be an effective means of practice, but that the positive effect may take time to develop.